Analisis Kualitatif Implementasi Four Eyes Principles Bank Syariah ( Study Kasus Sharia Business Unit BTN Syariah ) - Edy Junaedi (STAI Asy-Syukriyyah, 2018)
Purpose the present paper explores the application of the four eyes priciples to management decision in banking sector, a heretofore neglected area of business and management research. Methodology approach a theoritical analysis was first conducted of the four eyes principles. A qualitative field study of sharia business unit of Bank BTN. Non Performance Financing based on type shari’ah compliant contract of sharia business units and sharia commercial banks have shown that negative growth until 2017, four eyes principles is a model to make decision togather in financing. The requirement that a business transaction be approved by at least two individual who must both sign off on any significant financing decision Findings: from theoretical analysis, it can be conclude that the four eyes principles may generally conducted serve as a mechanism to mitigate risk of financing. Due to a non performing financing.